2008
DOI: 10.1002/esp.1666
|View full text |Cite
|
Sign up to set email alerts
|

The experimental basis for interpreting particle and magnetic fabrics of sheared till

Abstract: Particle fabrics of basal tills may allow testing of the bed-deformation model of glacier flow, which requires high bed shear strains (> > > > >100). Field studies, however, have not yielded a systematic relationship between shear-strain magnitude and fabric development. To isolate this relationship four basal tills and viscous putty were sheared in a ring-shear device to strains as high as 714. Fabric was characterized within a zone of shear deformation using the long-axis orientations of fine-gravel and sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
97
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 94 publications
8
97
2
Order By: Relevance
“…In contrast, other researchers have suggested that the clasts will initially rotate into the shear plane and then remain there (Hooyer and Iverson, 2000;Larsen and Piotrowski, 2003;Thomason and Iverson, 2006;Iverson et al, 2008). Thus the March (1932) model, which treats clasts as passive strain markers, is more appropriate.…”
Section: Introductionmentioning
confidence: 84%
“…In contrast, other researchers have suggested that the clasts will initially rotate into the shear plane and then remain there (Hooyer and Iverson, 2000;Larsen and Piotrowski, 2003;Thomason and Iverson, 2006;Iverson et al, 2008). Thus the March (1932) model, which treats clasts as passive strain markers, is more appropriate.…”
Section: Introductionmentioning
confidence: 84%
“…Similar connections between strain localization and frictional properties are emerging from studies of glacial till [e.g., Iverson et al, 2008;Rathbun et al, 2008]. However, most studies of till do not include direct information on friction constitutive behavior or stick-slip.…”
Section: Introductionmentioning
confidence: 92%
“…[45] Laboratory studies of till localization using anisotropy of magnetic susceptibility (AMS) fabric indicate that localization evolves until g on the order of 100 [Larsen et al, 2006;Thomason and Iverson, 2006;Iverson et al, 2008]. Unfortunately, these studies do not include data on the friction constitutive parameters for sheared till, and are all conducted in ring shear apparatuses.…”
Section: Dilation As a Proxy For Shear Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time field based observations thought to be indicative of deformation 50 style and cumulative shear strain need to be reconciled with apparently contradictory laboratory based 51 measurements of shearing style and magnitude (e.g. Iverson et al 1994Iverson et al , 1998Iverson et al , 2008 …”
mentioning
confidence: 99%